LITHOLOGY OF LITHOSPHERIC PLATES - Lisitsyn A.P. (My University, 2001)
The recent decades have become a "golden age" for lithology and marine geology. The principal achievements include investigation and mapping of oceanic bottom sediments and studies of the sedimentary material in the atmosphere, rivers, seas, and oceans, in ice and snow; development of a new approach to the role of biogenic processes; analysis of endogenic material supplied to the mid-ocean ridges; and changes in the view of sedimentary material of the land provenance and its transformation at the river-sea boundary. Another achievement is the concept of rapid ("avalanche") sedimentation at several levels, responsible for concentration of 93% of the sedimentary material of the Earth in limited basins, which become major reservoirs of hydrocarbons. The regions of avalanche sedimentation alternate with those of sedimentation gaps. The lithology is gaining a more solid quantitative basis, using such dynamic parameters as flux and vectors of sedimentary material. It has been found out that sedimentation in oceans follows its specific laws, as the oceanic crust differs from the continental crust. Modern lithological studies employ remote sensing methods (seismic stratigraphy, magnetometry, multiray sea beams, side-view sonars, etc.), as well as mapping and special sampling from natural bottom outcrops at depths of to 6000 m with the use of submersibles. Deep-sea drilling experiments (since 1968) and data processing performed by the joint efforts of international teams became an important step forward. As a result, the amount of data obtained in the course of the recent 30-40 years is hundreds or thousands of times as great as that accumulated through the whole previous history of the science, though lithologists, unfortunately, use very few of these data. The recent results led to numerous discoveries and creation of the mobilistic lithology, or the lithology of lithospheric plates, and required the synthetic use of the data of tectonics, geophysics, marine geology and geochemistry, petrology and petrochemistry, oceanology and climatology.